PENERAPAN KOMPOR MINYAK JELANTAH SEBAGAI SUBSTITUSI BAHAN BAKAR PADA INDUSTRI UMKM MAKANAN - Sanjaya, Ari Susandy; Sukmono, Yudi; Sitania, Farida Djumiati; Widada, Dharma; Wijaya, Muhammad Farhanuddin; Khiyarinnisa, Faza (LPPM Universitas Nusa Mandiri, 2025)
In daily life, stoves are essential tools used in cooking. They play an important role in energy use for households and small businesses, especially MSMEs (Micro, Small, and Medium Enterprises). In Samarinda and surrounding areas, food-related MSMEs are growing rapidly, ranging from snacks to trendy beverages. One of the major components of production costs is fuel. The 3-kg LPG cylinder, commonly called the